The role of information skewness in shaping extremist content: A look at four extremists - Waseem Afzal (Information Research: An International Electronic Journal)
Introduction. Extremism—distinct from activism—poses a serious threat to the healthy functioning of a society. In the contemporary world, the ability of extremists to spread their narratives using digital information environments has increased tremendously. Despite a substantial body of research on extremism, our understanding of the role of information and its properties in shaping extremist content is sketchy.